2022
DOI: 10.1101/2022.10.21.22281171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of the risk of hospitalisation among BA.1 and BA.2 COVID-19 cases treated with Sotrovimab in the community in England

Abstract: ObjectivesSotrovimab is one of several therapeutic agents that have been licensed to treat people at risk of severe outcomes following COVID-19 infection. However, there are concerns that it has reduced efficacy to treat people with the BA.2 sub-lineage of the Omicron (B.1.1.529) SARS-CoV-2 variant. We compared individuals with the BA.1 or BA.2 sub-lineage of the Omicron variant treated Sotrovimab in the community to assess their risk of hospital admission.MethodsWe performed a retrospective cohort study of in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 6 publications
1
61
0
Order By: Relevance
“…We recently showed that sotrovimab (S309) retained in vitro effector functions against BA.2 and conferred Fc-dependent protection in the lungs of mice infected with BA.2 67 . This preclinical finding is supported by the accumulation of real-world evidence suggesting that adverse clinical outcomes, such as hospitalization and mortality, remained consistently low during the BA.2 wave in patients treated with sotrovimab [68][69][70][71][72] . Here, we show that sotrovimab retained in vitro effector functions against all Omicron variants at levels comparable to those observed with Wu.…”
Section: Discussionmentioning
confidence: 70%
“…We recently showed that sotrovimab (S309) retained in vitro effector functions against BA.2 and conferred Fc-dependent protection in the lungs of mice infected with BA.2 67 . This preclinical finding is supported by the accumulation of real-world evidence suggesting that adverse clinical outcomes, such as hospitalization and mortality, remained consistently low during the BA.2 wave in patients treated with sotrovimab [68][69][70][71][72] . Here, we show that sotrovimab retained in vitro effector functions against all Omicron variants at levels comparable to those observed with Wu.…”
Section: Discussionmentioning
confidence: 70%
“…31 Moreover, sotrovimab was found to offer a similar level of protection against disease progression in patients with COVID-19 infected with the Omicron BA.1 and BA.2 subvariants. 32 Similarly, in an observational study in the US, treatment with sotrovimab was associated with a reduced risk of all-cause hospitalisation and mortality during the predominance of early Omicron variants. 33 This study has several limitations that should be considered.…”
Section: Discussionmentioning
confidence: 95%
“…30 The results of this study compliment other recent real-word studies on early treatments for COVID-19 in the UK. [31][32][33] For example, the findings of a recent publication on the comparative effectiveness of sotrovimab versus molnupiravir in England, conducted using the OpenSAFELY platform, showed that sotrovimab treatment was associated with a significant reduction in risk of severe COVID-19 outcomes in comparison to treatment with molnupiravir during BA.1 (primary analysis) and BA.2 (exploratory analysis) predominance. 31 Moreover, sotrovimab was found to offer a similar level of protection against disease progression in patients with COVID-19 infected with the Omicron BA.1 and BA.2 subvariants.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observational studies conducted in Europe suggest continued clinical effectiveness of sotrovimab through the Omicron BA.2 surge. In a study of >8000 patients in England, there were no differences in the risk of hospitalization for patients with mild to moderate COVID-19 treated with sotrovimab who were infected with the Omicron BA.1 or BA.2 SARS-CoV-2 variants [22].…”
Section: Introductionmentioning
confidence: 98%
“…These were progression of COVID-19 through Day 29 as defined by hospitalization >24 hours for acute management of illness due to any cause or death; or visit to a hospital emergency room for management of illness or hospitalization for acute management of illness for any duration and for any cause or death; development of severe COVID-19 requiring respiratory support including oxygen at Days 8, 15, 22 and 29; and the incidence of participants requiring intensive care unit (ICU) stay or mechanical ventilation through Day 29. Viral load in nasal secretions was assessed using quantitative RT-PCR and evaluated as the change from baseline in viral load atDays 3,5,8,11,15,22,and 29; undetectable SARS-CoV-2 in nasal secretions atDays 3,5,8,11,15,22,and 29; and the proportion of participants with a persistently high SARS-CoV-2 viral load (≥4.1 log 10 copies/mL) at Day 8.…”
mentioning
confidence: 99%